2021
DOI: 10.3389/fimmu.2021.574967
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Function of Vitamin D and Its Role in Autoimmune Thyroid Disease

Abstract: Vitamin D is one of the most important nutrients required by the human body. It is a steroid hormone that plays an important role in regulating calcium and phosphorus metabolism, and bone health. Epidemiological studies have revealed a close correlation between vitamin D and many common chronic diseases. Additionally, vitamin D has recently been shown to act as an immunomodulatory hormone, and, accordingly, vitamin D deficiency was uncovered as a risk factor for autoimmune thyroid diseases, although the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 65 publications
1
55
0
3
Order By: Relevance
“…Via what mechanism does vitamin D deficiency contribute to hypothyroxinaemia is unknown. The well documented immunomodulatory function of vitamin D and the contribution of vitamin D deficiency to autoimmune thyroid disease [31] should be neglected, as IH is repeatedly found in the literature to be not associated with thyroid antibodies [2]. Consistently, none of our patients with IH had positive thyroid antibodies.…”
Section: Discussionsupporting
confidence: 48%
“…Via what mechanism does vitamin D deficiency contribute to hypothyroxinaemia is unknown. The well documented immunomodulatory function of vitamin D and the contribution of vitamin D deficiency to autoimmune thyroid disease [31] should be neglected, as IH is repeatedly found in the literature to be not associated with thyroid antibodies [2]. Consistently, none of our patients with IH had positive thyroid antibodies.…”
Section: Discussionsupporting
confidence: 48%
“…Припускають, що автоімунні захворювання, включно з цукровим діабетом (ЦД) 1-го типу, автоімунним тиреоїдитом (АІТ), запальними захворюваннями кишечника, ревматоїдним артритом, системним червоним вовчаком і розсіяним склерозом, можуть бути пов'язані з дисбалансом VD. У цьому контексті VD може відігравати важливу роль у модуляції вродженого й адаптивного імунітету [1,7,9].…”
Section: імуномодулюючі властивості Vdunclassified
“…З огляду на імуномодулюючу роль VD його зв'язок з AIT інтенсивно вивчається останніми роками [7,18]. Відомо, що VD посилює вроджену імунну відповідь, одночасно пригнічуючи адаптивну імунну систему [1,9,22]. Активований VD (кальцитріол) модулює цитокіновий пул від прозапального до більш толерогенного імунного статусу.…”
Section: вітамін D і автоімунні захворювання щитоподібної залозиunclassified
“…Host immune responses to respiratory viruses are important in asthma exacerbations. Mechanistic studies have identified immunomodulatory and anti-inflammatory roles for vitamin D [ 4 , 5 ]. Figure 1 describes the actions of vitamin D on B-cells, T-cells and activated mast cells in the context of an allergen/virus-induced exacerbation of asthma.…”
Section: Contextmentioning
confidence: 99%